SINGLE PARENT INSPIRATIF: PERSPEKTIF TAFSIR MAQASHIDI (STUDI KISAH MARYAM DALAM AL-QURAN) - Ainul Falah, Zulaiha; Ikhwanuddin, Ikhwanuddin; Prasetiawati, Eka (Institut Agama Islam Ngawi, 2024)
The increasing number of divorce cases in Indonesia has led to many family problems, such as single parenthood, where many mothers raise their children alone without the role of a husband. This study aims to motivate single parents, especially mothers, by examining the story of Maryam in the Qur'an using thematic and maqashidi interpretation methods, focusing on Q.S Ali 'Imran [3]: 35-36 and Q.S Maryam [19]: 16-23, 29. This qualitative research uses primary sources from Al-Azhar, Al-Misbah, and Ibn Kathir's interpretations. The results reveal that women have been equal to men since ancient times, and in modern times, women are increasingly developing and daring to compete without fear. Maryam, as an inspirational single parent, demonstrates resilience in raising her son without the role of a husband, despite facing slander and insults from her people. Maryam's courage to reveal the truth and present her son to her people serves as a motivation for single parents, especially mothers, to be patient, strong, and persistent for the future of their children under their responsibility. Keywords: Inspirational Single Parent, Mufassir's Views, Maqashidi